Prescription Adverse Drug Events System (PrescADE) Based on Ontology and Internet of Things. (3rd October 2018) - Nakhla, Zina; Nouira, Kaouther; Ferchichi, Ahmed
Abstract: Internet of Things (IoT) is a growing technology that widely applied to interconnect available medical resources and provide reliable, effective and smart healthcare service to patients. The quality of healthcare is measured by the potential of occurrence of medical errors, cost shrinkage and high speed. This paper proposes a new system to prevent Adverse Drug Events (ADEs) which is a kind medical errors very propagated in health facilities. The proposed system focus on ADE in prescription stage called Prescription ADE system (PrescADE). It improves patient safety, reduces ADE and optimizes the healthcare process. It based on ADE ontology, on IoT and a set of rules to analyze prescription and help doctors. For experimentations, a platform is developed to test rules using 20 patients and three doctors. We compared our proposed system to Computerized Prescriber Order Entry system (CPOE) which is a system to detect ADE of prescription and widely used in hospitals. The results show that PrescADE system has better performance than CPOE system in terms of prescription time and ADE detected. PrescADE detects 314% of ADEs higher than CPOE and 82% of prescription time lower than CPOE.